O impeachment de 2016 no Jornal Nacional: análise dos discursos antagonistas na polarização política - Ribeiro, Pedro Simon Camarão Telles (2020)
This research analyzes the meanings constructed by the journalistic coverage of the Jornal Nacional (JN) on the Brazilian political crisis in 2016, in the months of March, April, August and September of that year, when the impeachment votes in the National Congress took place, also a series of demonstrations in favor of and against the current government, as well as accusations of corruption schemes involving Luiz Inácio Lula da Silva and other members of the Partido dos Trabalhadores. The research adopts Laclau and Mouffe's (1985) discourse theory - which has post-structuralism as a reference - and analyses of the political crisis carried out by Alonso (2017) and Prado (2019) to identify the chains of meaning that the polarized social groups constituted, the dispute between antagonist discourses as presented by the TVnews and the way JN assumed a political position. The methodology of television analysis built by Beatriz Becker (2012) was used to deconstruct characteristics, such as the construction of a polarized narrative, based on conflict and with a conservative character, of the National Journal present in the political news, which presented to its audience the struggles between different social groups